Arcasia heritage volume one - Ahmed, Abu Sayeed M.; Architects Regional Council, Asia(ARCASIA) (Dhaka, Bangladesh : ARCASIA, 2010)
The Arcasia heritage is a portfolio of some heritage architectural projects from the ARCASIA member countries. It is a collection documenting ten heritage projects from each of the seventeen member countries of ARCASIA. These projects have been selected such that they signify a particular period of architectural achievement, covering from ancient to modern age. The total book is devided into two volumes, the first one containing eight countries while the second volume includes nine countries, all of them being arranged in alphabetical order. However, to each country, the projects have been presented according to the time line. Valuable drawings and photographs have enriched the textual content of the publication
"October 2010'--T.p. verso.
ARC
ARCASIA Heritage Book
Keywords: Architecture -- Asia; Architecture